Evaluation of Malaysian Rice Genotypes for Adaptability in Zinc Deficient Soil - Hafeezullah, Babar (2010)
Significant increase in rice production is required to provide sufficient rice for the growing population. Among other factors, Zn deficiency also contributes to the low rice yield. Zn deficiency in rice production is widespread globally and study of Zn nutrition in rice production in Malaysia is limited. This study was undertaken to determine the Zn status of Malaysian rice soils, to evaluate the Zn efficiency of selected rice genotypes and to determine the response of Zn application and the Zn residual effect on the growth and yield of rice in the field. Soil samples of 15 soil series (Kranji, Sedaka, Guar, Kundur, Tualang, Teluk Chengai, Kuala Kedah, Rotan, Sedu, Kangkong, Batu Hitam, Lubok Itek, Tepus, Telemong-Akob and Champaka) were collected from paddy growing areas in Kedah and Kelantan, Malaysia and their Zn status were determined. These samples were taken from 3 different depths (0 -15 cm, 15 – 30 cm and 30 - 45cm). The Zn concentrations of the 15 soil series were found to be significantly different at different depths and locations, and the concentration ranged between 0.22 to 2.64 μg g-1. Thirty one rice genotypes were obtained from the Malaysian Agricultural Research Development Institute (MARDI) for the determination of Zn concentration in husked and unhusked rice. The Zn concentration in the husked rice indicated that 18 out of 31 rice genotypes were below the critical limit (< 20μg g -1) of Zn concentration. Zinc concentrations in all genotypes were found to be significantly lower after dehusking. However, minimum differences between husked and unhusked rice were observed in SM2 and MR 106 genotypes. The Zn efficiency of ten rice genotypes ( Kadaria, MR 219, MR 220, MR 211,Bahagia, Seri Malaysia Dua, MR 185, MR 106, MRQ 74 and Jaya) were studied by using three levels (0.007, 0.035, and 3.5 mg L-1) of Zn under hydroponic culture. Zn efficiency among the genotypes varied from 45.4 to 87.4%. Seri Malaysia Dua and MR 106 were ranked as Zn efficient while Jaya, MRQ 74, MR211 and Bahagia were ranked as Zn inefficient rice genotypes. To confirm the results of the hydroponic culture study, a glasshouse and two continuous seasons of field experiments were conducted in Kangkong soil series which has low Zn status. Each experiment was conducted using 6 rice genotypes (Seri Malaysia Dua, MR 106, MR 219, MR 220, MR 211 and Bahagia) with two levels (0 and 15 kg ha-1) of Zn. The results from glasshouseand two continuous seasons of field experiment showed that SM2 and MR 106 genotypes were Zn efficient, MR 219 and MR 220 were moderately efficient, and MR 211 and Bahagia were Zn inefficient rice genotypes. The results from field study revealed that Zn application increased yield of all rice genotypes between 16.2% and 47.5%. It was found that the Zn efficient rice genotype MR 106 produced better yield with no Zn application as compared to the other rice genotypes. Based on the results obtained in this study it is concluded that soils of rice growing areas in Kedah and Kelantan were low in Zn content. The Zn efficient rice genotypes, especially the MR 106, have the ability to grow well without Zn application in submerged acid soil, and only loss very little Zn after de-husking.